Psychometric characterization of incidental feedback sources during grasping with a hand prosthesis - Meike Wilke and Christian Niethammer and Britta Meyer and Dario Farina and Strahinja Dosen (Journal of NeuroEngineering and Rehabilitation, 2019)
Background